Eksplorasi Bakteri Asam Laktat dengan Aktivitas Antibakteri dari Urutan sebagai Kandidat Probiotik - Dwijastuti, Ni Made Sri (Department of Health Analyst, Politeknik Kesehatan, Kementerian Kesehatan Tanjungkarang, 2023)
Lactic Acid Bacteria (LAB) species grow naturally during the fermentation process of Urutans. This research aims to isolate LAB from Urutan and study its ability to inhibit pathogenic bacteria. According to FAO/WHO, antagonistic activity against enteric pathogenic microbes is one of the criteria for probiotic products. The research was conducted with an exploratory method at the Microbiology Laboratory of the Faculty of Medicine, Udayana University, from February to June 2020. The research samples were five Urutans from Urutan traders in Baturiti District, Tabanan-Bali. LAB was isolated using MRS agar media supplemented with 1% CaCO3. LAB suspects were further confirmed by catalase test and Gram staining. The results showed 326 isolates confirmed as LAB colonies with the characteristics of acidifying growth media, catalase-negative, and Gram-positive rods and cocci. Antibacterial activity test on isolates confirmed as LAB showed that 29 isolates inhibited Escherichia coli and 46 isolates inhibited Staphylococcus aureus. A total of 158 other isolates inhibited the growth of E.coli, and S. aureus, and 93 isolates showed no inhibitory activity on both. 158 LAB isolates that inhibit E.coli and S.aureus could be further studied and developed as probiotic candidates.